Social enterprise in Germany: between institutional inertia, innovation and cooperation - Göler von Ravensburg, Nicole; Mildenberger, Georg; Krlev, Gorgi (Social enterprise in western Europe, 2021)
This chapter outlines the main discussion lines and models of what could be considered as social enterprise according to the indicators that make up the EMES Network's approach of the ideal-typical social enterprise. These indicators have been used as a common frame of analysis within the ICSEM Project. It discusses the current promotion of SE initiatives by public authorities as well as the general societal and the most relevant socio-economic conditions they face. As their numbers are greatest in the welfare sector, the chapter focuses assessment of potentials and likely future trends in this sector. Generally speaking, the German cooperative history has been more oriented towards small and medium enterprises and farmers than towards the working class. In Germany, two different types of social enterprise offer opportunities for labour-market integration and work inclusion to two more or less distinct groups of people: people with disabilities and people with other labour-market handicaps.